1990
DOI: 10.1111/j.1600-0765.1990.tb01036.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of cementoblasts in the resorbant organ of human deciduous teeth during root resorption

Abstract: Human deciduous teeth undergoing physiologic root resorption were extracted and fixed with a mixture of formaldehyde and glutaraldehyde and processed for scanning (SEM) and transmission (TEM) electron microscopy, and for acid (ACPase) and alkaline phosphatase (ALPase) cytochemistry. The resorbant organ, rich in odontoclasts, cementoblasts, fibroblasts, and macrophages, formed prominent resorption lacunae in root dentin. SEM observations of resorption lacunae treated with trypsin solution showed islands of newl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
4

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 42 publications
1
18
0
4
Order By: Relevance
“…Thus, some authors considered that these mononuclear cells might scavenge the bone surface at the end of osteoclastic resorption (Heersche, 1978; Tran Van et al, 1982;Everts et al, 2002) and that the cement line/reversal line seen on the resorbed surface might be formed by these mononuclear cells (Heersche, 1978; Tran Van et al, 1982;McKee and Nanci, 1996a;Everts et al, 2002). In the case of tooth resorption, it was also reported that similar kinds of mononuclear cell types, e.g., cementoblast-like cells (Sasaki et al, 1990), machrophage-like cells or fibroblast-like cells (Tanaka et al, 1990;Okamura et al, 1993), and a special class of mononuclear cells (Bosshardt and Schroeder, 1998) were seen lining the resorption surface. In the present study, we also found that numerous mononuclear cells was seen to populate the resorbed enamel surface after the withdrawal of the odontoclasts and prior to the onset of repair cementum-like tissue formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, some authors considered that these mononuclear cells might scavenge the bone surface at the end of osteoclastic resorption (Heersche, 1978; Tran Van et al, 1982;Everts et al, 2002) and that the cement line/reversal line seen on the resorbed surface might be formed by these mononuclear cells (Heersche, 1978; Tran Van et al, 1982;McKee and Nanci, 1996a;Everts et al, 2002). In the case of tooth resorption, it was also reported that similar kinds of mononuclear cell types, e.g., cementoblast-like cells (Sasaki et al, 1990), machrophage-like cells or fibroblast-like cells (Tanaka et al, 1990;Okamura et al, 1993), and a special class of mononuclear cells (Bosshardt and Schroeder, 1998) were seen lining the resorption surface. In the present study, we also found that numerous mononuclear cells was seen to populate the resorbed enamel surface after the withdrawal of the odontoclasts and prior to the onset of repair cementum-like tissue formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, tooth resorption occasionally takes place under pathological conditions such as infection, trauma, or tumor development (Andreasen, 1988;Tronstad, 1988). It is well known that after cessation of tooth resorption, the area resorbed is rapidly repaired by the deposition of cementum or cementum-like tissue (Orban, 1928;Mueller, 1931; Kronfeld, 1932;Henry and Weinmann, 1951;Furseth, 1968;Schroeder, 1986;Sasaki et al, 1990;Sahara et al, 1992Sahara et al, , 1993Bosshardt and Schroeder, 1994;Kimura et al, 2003). This site-specific localization of repair seems to resemble that found in bone formation during bone remodeling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research groups reported that the resorbed dentin surface is rapidly covered with cementum-like tissue after the cessation of tooth resorption (FUR-SETH, 1968;SOSKOLNE and BIMSTEIN, 1977;ROLLING, 1981;SASAKI et al, 1990b;SAHARA et al, 1992SAHARA et al, , 1993YAWAKA et al, 1995). SAHARA and SUZUKI (1993) reported on the cellular events during the resorption and repair processes of human deciduous teeth, and pointed out the occurrence of numerous mononuclear cells having many lysosomes and cytoplasmic vesicles reactive for TRACPase and non-specific esterase activities.…”
Section: This Immunocytochemicalmentioning
confidence: 99%
“…Thus, the extraction of those teeth with a thinner PDL may also have injured the cementoblasts, which resulted in the inhibition of repair of the root after replantation. 32 On the other hand, Herr et al 33 have reported that fibroblasts originating from both the remaining PDL and alveolar bone compartments functioned to repair the periodontium, but cells migrating to the root surface most likely originated from the PDL. This supports the concept that the PDL attached to the extracted tooth could be another key factor for periodontal healing after replantation or transplantation.…”
Section: Discussionmentioning
confidence: 99%